In situ templating synthesis of conic Ba0.5Sr 0.5Co0.8Fe0.2O3-d perovskite at elevated temperature - Zhou, W.; Ran, R.; Shao, Zongping; Jin, W. (Indian Academy of Sciences, 2009)
Conic Ba0-5Sr0-5Co0-8Fe 0-2O3-d (BSCF) functional composite oxide was synthesized via a simple in situ templating process. The treatment of the solid precursor with concentrated nitric acid resulted in the mismatch of ionic radius at A-site and B-site of the ABO3 perovskite, due to the oxidation of cobalt/iron ions, and the formation of Ba0-5Sr0-5(NO 3)2 solid solution. Therefore, instead of the direct formation of BSCF oxide, an intermediate phase of Ba0-5Sr 0-5CoO3 (BSC) in hexagonal lattice structure and with conic particle shape was preferentially formed during calcination at low temperature. BSCF perovskite was then produced by the in situ templating of BSC with iron diffusing into the BSC lattice during calcination at high temperature. Wellcrystallized BSCF particles in conic shape were obtained by the calcination of the nitric acid treated precursor at 900°C. © Indian Academy of Sciences.